HTML5 games novice to ninja - Castledine, Earle (SitePoint, 2018)
This book will teach you how to create awesome video games. Games from scratch. Games that run cross-platform, in web browsers, and on phones. Games filled with dynamic sound and music. Games overflowing with impressive visual effects. Fun games. More importantly, this book will teach you how to think about making games. You'll learn to analyze and dissect games; to understand what it is that makes great games great. By the end of the journey you'll have all the knowledge and tools needed to produce engaging, polished products that people will love to play. Learn the basics: game loops and input, Draw graphics on the screen using Canvas, Add amazing sound effects and music using the Web Audio API, Develop several fun games: a platformer, a shoot ‘em up, a dungeon crawler, and a physics-based game, Create your own JavaScript game library, Jazz up your game up with "juice": screen shakes, particle effects, and more.